Perencanaan Desain Offshore Kontruksi Bawah Laut menggunakan Pengolahan Data Pemodelan Geofisika dengan Program Simulasi 3D Surfer - Edy Soesanto; Aly Rasyid; Hadi Suyanto (Department of Petroleum Engineering, 2022)
Abstract Underwater construction design planning is increasingly being developed as a 3D modeling simulation, because 3D simulation is expected to be able to make the initial plan for making a design framework. Surfer is one of the software that was created for the purpose of making contour maps and three-dimensional modeling based on existing grids and simplifying and accelerating data conversion activities into the form of contour maps and surface plots. One of the applications is Surfer in the field of Underwater Technology development is 3D modeling simulation and bathymetric contour map making, sediment layer modeling using SBP data and making current stick plots to determine circulation and current velocity and direction. In addition, Surfer can also display maps in 2D or 3D. on this occasion Surfer 16 software will be used to process marine acoustic data with X (Easting) data, Y (Northing) data and six Z layer depths, namely Z1-Z6, the data is processed in one step to make 2D and 3D models which are then will be interpreted as a simulation material for the initial planning of the underwater construction design. Keywords: design, offshore, construction, underwater, surfer Abstrak Perencanaan desain kontruksi bawah laut semakain banyak dikembangkan sebagai simulasi pemodelan 3D, karena simulasi 3D diharapkan dapat menjadikan rencana awal pembuatan kerangka desain. Surfer adalah salah satu dari perangkat lunak yang diciptakan untuk kegunaan pembuatan peta kontur dan pemodelan tiga dimensi yang berdasarkan grid yang ada dan mempermudah serta mempercepat akvitas konversi data ke dalam bentuk peta kontur dan plot permukaan. Salah satu aplikasi adalah Surfer dalam bidang pengembangan Teknologi Bawah laut adalah simulasi pemodelan 3D dan pembuatan peta kontur batimetri, pemodelan lapisan sedimen melalui data SBP dan pembuatan stick plot arus untuk mengetahui sirkulasi dan kecepatan dan arah arus. Selain itu, Surfer juga dapat menampilkan peta secara 2D ataupun 3D. pada kesempatan ini software Surfer 16 yang akan digunakan unutk mengolah data akustik kelautan dengan data X (Easting) ,data Y (Northing) dan enam kedalaman lapisan Z yaitu Z1-Z6, data tersebut diproses dengan sebuah tahapan untuk menjadikan model 2D dan 3D yang selanjutnya akan di interpretasi sebagai bahan simulasi perencanaan awal desain kontruksi bawah laut. Kata kunci: desain, offshore, kuntruksi, bawah laut, surfer Reference: Septina Anggiani. Pengolahan data oseanografi dengan surfer 10.0 dan odv 4.0 Surya, Yohanes Sam. 2008. Surfer8.http://www.gis4u.net [26 November2013] International Hydrographic Organization (IHO) Standard for Hydrographic Surveys, Special Publication No.44 (SP.44), 5th Edition, February 2008 Alba, J. L. and Audibert, J. M. E. (1999). “Pile design in calcareous and carbonaceous granular materials: a historical overview”, Second International Conference Engineering on for Calcareous Sediments, Bahrain American Petroleum Institute (2000). “Recommended practice for planning, designing, and constructing fixed offshore platforms-working stress design”, API Recommended Practice 2A-WSD (RP 2A-WSD), (21’‘ ed.). API, Washington, D.C Anderson, D. G. and Stokoe, K. H. (1978). “Shear modulus: a time-dependent soil property”, Dynamic Geotechnical Testing, ASTM STP 654, American Society for Testing and Materials, pp. 66-90. Angemeer, J., Carlson, E. D., and Klick, J. H. (1973). “Techniques and results of offshore pile load testing in calcareous soils”, Proceedings, Ffth Offshore Technology Conference, Houston, Vol. 2, pp. 677-692 Bogard, J. D. and Matlock, H. (1990). “Application of model pile tests to axial pile design”, Proceedings, Twenty-Second Annual Offshore Technology Conference, Houston, Paper No. 6376 Coyle, H. M. and Gibson, G. C. (1970). “Empirical damping constants for sands and clays”. Journal, Soil Mechanics and Foundations Division, ASCE, Vol. 96, No. SM3, pp. 949-965. Cox, W. R. and Reese, L. C. (1976). “Pullout tests of grouted piles in stiff”, Proceedings, Eighth Offshore Technology Conference, OTC 2473, Houston, Vol. 2, pp. 539-55 1 Datta, M., Gulhati, S. K., and Rao, G. V. (1980). “An appraisal of the existing practice of determining the axial load capacity of deep penetration piles in calcareous sands”, Proceedings, Twelfth Offshore Technology Conference, Houston, Vol. 4, pp. 1 19-1 30